Mediation using CB-SEM: a practical guideline - Rahman, Md. Mizanur; Ali, Noor Azman; Jantan, Amer Hamzah; Samuel, Adedeji Babatunji; Rahaman, Md. Saidur (Inderscience Publishers, 2021)
This research paper has tried to attend to the thought provoking issues about mediation analysis (MA) using covariance-based structural equation modelling (CB-SEM) with setting an example that is work family balance (WFB) may mediate (full, partial or no) the relationship between work-family conflict (W to FC and F to WC) and job satisfaction (JS). Notably, the emphasis is on four critical burning aspects regarding current literature on MA with the necessary commands and interpretations. Based on informed decisions, updating of knowledge from the present citations included will provide benefits of carrying out a proper study by researchers. Consciousness concerning the challenges and uses of the CB-SEM as an analytical tool for MA in the social and behavioural sciences and its significance at later time is for better appreciation of the technique. Besides the rationalisation as a method for analysing research data, the study introduced practical examples to enhance the application of the method further.